2023
DOI: 10.1186/s12888-023-04733-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anxiety and depression among university teachers during third wave of COVID-19

Abstract: Background To estimate the determinants of anxiety and depression among university teachers in Lahore, Pakistan, during COVID-19. Methods A cross-sectional study was conducted by enrolling 668 teachers from the universities of Lahore, Pakistan. Data were collected using a questionnaire. Chi-square for significance and logistic regression for the association were used. Results Majorly, the university te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, Nader Salari and others found that during the COVID-19, the prevalence of depression among nursing staff caring for patients was 24.3%, and the prevalence of anxiety was 25.8% [ 14 ], Naser Parizad found that the mean job stress of ICU nurses was ‘moderate’ [ 15 ]. Hamid Saeed et al found that university teachers also experienced more severe anxiety and depression [ 16 ]. Scholars have also shown that 57% and 33% of farmers were classified as possible and possible cases for anxiety, respectively; the prospective recommendations for depression were 34% and 15% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nader Salari and others found that during the COVID-19, the prevalence of depression among nursing staff caring for patients was 24.3%, and the prevalence of anxiety was 25.8% [ 14 ], Naser Parizad found that the mean job stress of ICU nurses was ‘moderate’ [ 15 ]. Hamid Saeed et al found that university teachers also experienced more severe anxiety and depression [ 16 ]. Scholars have also shown that 57% and 33% of farmers were classified as possible and possible cases for anxiety, respectively; the prospective recommendations for depression were 34% and 15% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%